Amido Silicon Chalcogenide Compounds with Unprecedented Cluster Cores and Low Oxidation State Silicon Atoms. Issue 44 (19th September 2019) - Schwedtmann, Kevin; Hepp, Alexander; Schwedtmann, Kai; Weigand, Jan J.; Lips, Felicitas
Abstract : Reactions of the bicyclic silicon(I) ring compound [Si4 {N(SiMe3 )Dipp}4 ] 1 with the chalcogens O2, Se, Te and the group 16 element compounds TeP( n Bu)3 and Me3 NO afforded unprecedented amido‐substituted cage compounds such as [Si4 Se3 {N(SiMe3 )Dipp}4 ] 3–5 with two different tricyclo‐heptane‐type cages and one with a defect‐hetero‐cubane‐type Si4 Se3 core, and [Si4 Te6 {N(SiMe3 )Dipp}4 ] 6 with an adamantane‐type cage. These compounds were examined by single‐crystal X‐ray diffraction, multinuclear NMR spectroscopy in solution, ESI mass spectrometry, UV/Vis spectroscopy, and DFT calculations. Abstract : Bicyclic silicon(I) ring compound [Si4 {N(SiMe3 )Dipp}4 ] 1 reacts with Se(red), Se(gray), and TeP( n Bu)3 at room temp. or in refluxing toluene to yield amido‐substituted silicon chalcogenides with unprecedented cage motifs and different low oxidation states of the Si atoms. Silicon selenides 3–5 and a telluride 6 with novel cage motifs were comprehensively investigated.